Transmissive diamond photocathodes - Foord, J; Lau, C; Hirarnatsu, M (2005)
The first studies are reported on the characteristics of ultra-violet transmissive mode, CVD diamond photocathodes, in which photoelectrons are emitted from a diamond membrane via the opposite interface from that of the incident radiation. For membranes in the thickness range 5-40 μm, the transmissive photoyield at threshold wavelengths is shown to be less but comparable to that measured for reflective, thick film diamond photocathodes. The characteristics are found to be insensitive to the phase purity of differing diamond membranes used, but are very dependent on whether the growth or substrate interfaces of the diamond membrane face the incident UV radiation. The factors influencing the characteristics observed are discussed. © 2005 Elsevier Ltd. All rights reserved.